Nitroisobenzofuranone, a small molecule inhibitor of multidrug-resistant Staphylococcus aureus, targets peptidoglycan biosynthesis. Issue 83 (29th September 2022) - Rawat, Viral; Tiwari, Sona; Khanna, Shweta; Gupta, Umang; S. N. C., Sridhar; Yadav, Dharmendra K.; Kaul, Grace; Akhir, Abdul; Saxena, Deepanshi; Matheshwaran, Saravanan; Chopra, Sidharth; Allimuthu, Dharmaraja
Abstract : To target antimicrobial resistance, 4-nitroisobenzofuran-1(3 H )-one (IITK2020), is presented as an exclusive inhibitor of S. aureus including drug-resistant S. aureus clinical strains, that prevents peptidoglycan biosynthesis. Abstract : Antimicrobial resistance (AMR) is a global health concern. Targetting AMR, we present an in situ lactonization mechanism generating 4-nitroisobenzofuran-1(3 H )-one (IITK2020 ), an exclusive S. aureus inhibitor at 2–4 μg mL −1 MIC including multidrug-resistant S. aureus clinical strains, that prevents peptidoglycan biosynthesis.